GRACE-derived land-hydrological mass changes and their impact on relative sea-level variations - Baur, O.; Kuhn, Michael; Featherstone, Will (Oesterreichische Gesellschaft fuer Vermessung und Geoiformation und Oesterreichische Geodaetische Kommission, 2011)
The GRACE (Gravity Recovery And Climate Experiment) mission allows inference of mass variations on, above and beneath the Earth’s surface from gravitational signatures in space. We present a robust and straightforward procedure to derive mass changes from time-variable gravity field estimates. We outline our solution to the leakage problem and shed light on linear versus accelerated secular-change modeling. Based on a six-year gravity field time-series from March 2003 to February 2009, we provide detailed analysis of two selected areas, Greenland and the Orinoco Basin. As a result, annual Greenland mass loss accelerated by +21.3±3 Gt/yr2 during the six-year period. Furthermore, we show the impact of recent ice melting on global relative sea level. In terms of uniform change, the contributions of Greenland and Antarctica are +0.56±0.01 mm/yr and +0.50±0.07 mm/yr, respectively. However, we prove that simplistic uniform modeling of sea-level variations is insufficient as it disregards the gravitational feedback effect caused by mass redistribution.